Sensor projects with Raspberry Pi internet of things and digital image processing - Guillen, Guillermo (Apress, 2024)
Use Python to develop Rasperry Pi projects to solve common digital image processing and IoT problems. Using a free IoT server you'll tackle fundamental topics and concepts behind theses two areas. This second edition includes new content on Artificial Intelligence and updated sensor guidance to help you better explore virtual animations, create a homemade spectrometer, and master object classification with Edge Impulse. Start by creating a system to detect movement with a PIR motion sensor and a Raspberry Pi board. Use the MQ2 gas sensor and a Raspberry Pi board as a gas leak alarm system to detect dangerous explosive and fire hazards. Then train your system to send the captured data to the remote server ThingSpeak. You'll also develop a weather station with your Raspberry Pi. Using the DHT11 (humidity and temperature sensor) and BMP (barometric pressure and temperature sensor) in conjunction with ThingSpeak and X, you can receive real time weather alerts from your own meterological system! Spectral sensers used with the Raspberry Pi include the AS7262 (six colors), and AS7263 (near infrared) for the construction of a filter spectrometer, sensing colored solutions, and assessing plant foliage health. Finally, expand your skills into the popular machine learning world of digital image processing using OpenCV and a Pi. Make your own object classifiers and finally manipulate an object by means of an image in movement. This skillset has many applications, ranging from recognizing people or objects, to creating your own video surveillance system. With the skills gained from Sensor Projects with Raspberry Pi, you'll be well-equipped to explore other applications in mobile development and electrical engineering as well.
Includes bibliographical references and index
Keywords: Raspberry Pi (Computer); Python (Computer program language); Detectors; Internet of things; Raspberry Pi (Ordinateur); Python (Langage de programmation); Internet des objets